Clinical, Cytological, Histopathological and Immunohistochemical Features of a T-Zone Lymphoma in a Mixed-Breed Dog - Monteiro, Mariana Cunha; Gorza, Leonardo Lima; Merísio, Alice Correa; Flecher, Mayra Cunha; Horta, Rodrigo dos Santos (Acta Scientiae Veterinariae, 2020)
Background: Non-Hodgkin lymphoma are a group of lymphoid neoplasms originated from the proliferation of precursors or mature, T, B and/ or NK lymphocytes. T-Zone lymphoma (TZL) is characterized as an indolent lymphoma due to its slow progression and poor chemotherapy´s response. Dogs affected by this neoplasm may live for many years without clinical signs and are often underdiagnosed. The aim of the present article is report a TZL case in a nine-year old male mixed breed dog, submitted to clinical follow-up and chemotherapy. Case: A nine-year old male mixed-breed dog was presented due to the observation of an increased left mandibular lymph node. The previous cytological examination was suggestive of reactive hyperplasia and histopathological examination, by incisional biopsy, compatible with lymphocytic low-grade lymphoma. Physical examination revealed enlarged and firm left mandibular lymph node and adequate physical condition. A cytological examination was performed in the mandibular and both popliteal lymph nodes and revealed many small lymphocytes with hyperchromatic chromatin, rarely evident nucleolus and whose cytoplasm often projected in the form of a “hind-mirror” or “comet tail”, compatible with lymphocytic lymphoma (low grade) and suggestive of TZL, in the both lymph nodes. The histopathological and immunohistochemical examination, of the mandibular lymph node, were chosen to confirm the diagnosis. At histopathology it was observed 40% of the sample contained a monotonous cell population, composed by small lymphocytes, with some presenting “hand-mirror” morphology. Two mitotic figures were evidenced per field of high magnification (40x), inferring a low-grade disease. Immunohistochemical analysis revealed neoplastic proliferation with immunolabeling of CD3 lymphocytes and positivity for Ki-67, but negative for CD20, CD79a, CD45, MUM-1 and PAX-5. Although there is no consensus about requirements and treatment´s efficacy, it has been chosen to treat the dog with chlorambucil, because of the elevated Ki-67 value (48%). The patient obtained a free-progression interval higher than 820 days, from the earlier investigations of lymphadenopathy, with excellent quality of life and no side effects related to the use of chlorambucil. Discussion: Although TZL is a common subtype of lymphoproliferative disease in dog, it is still underdiagnosed. The TZL diagnosis can be suggested by cytology, from the disclosures in neoplastic cells of a cytoplasmic projections, recognized as a “hand-mirror” or “comet tail”, corroborated with the present case, however the histopathology is confirmatory. Immunohistochemistry in which the neoplasm cells showed a positive immunolabeling for CD3 and negative for CD79a, CD20, CD45, MUM1 and PAX5, as evidenced in this report, confirming the T-cell origin. According to the literature, lymphomas composed by small clear cells and cytoplasm projecting by cytology, immunolabeling CD3 and CD25 positive and CD45 negative are, together, findings that confirmed TZL. The biological behaviour of indolent lymphoma is still largely unknown, however the prognosis of dogs, with indolent lymphoma of T or B cells, seems to be favourable. Studies showed different days of median overall survival, such as 760 days and 4.4 years. In the present case, the dog showed 820 days, confirming the good prognosis and an indolent behavoiur. Aggressive chemotherapy protocols are not necessary for such cases and the treatment with chlorambucil, without the association of prednisolone, has been well tolerated by the patient, which showed no side effects until the moment.